Environment-related health risks, knowledge and awareness among people in precarious milieus: secondary data analysis from the German "Environmental Awareness Study" - Annabell Duda; Doreen Reifegerste (Frontiers Media S.A., 2024)
IntroductionPrecarious milieus more frequently suffer from environmental risks and show lower environmental awareness and behavior than other milieus in the German population. This study investigates the factors that influence environmental awareness in precarious milieus and the roles of environmental knowledge and the perception of environment-related health burdens.MethodsA quantitative secondary data analysis of the German Environmental Awareness Study 2018 (N = 2017) was used to analyze the perception of environmental health burdens, environmental knowledge, and environmental awareness between precarious milieus (n = 190) and seven other milieus. One-way analysis of variance (ANOVA) and Bonferroni post hoc tests were used for this purpose. More in-depth analyses of the precarious milieus were carried out using multiple regression analyses.ResultsThere were significant differences in the perceptions of environmental health burdens affected by rail-traffic noise and neighborhood noise. Furthermore, environmental knowledge in precarious milieus was significantly lower than in five out of the seven other milieus (all p < 0.001) and was significantly associated with environmental cognition and gender. Precarious milieus had higher environmental affect than established milieus but less than that of critical-creative milieus and young idealists (all p < 0.001). Environmental cognition and environmental behavior were significantly associated with environmental affect. Environmental cognition was significantly higher in precarious milieus than in established milieus and among young pragmatists but was lower than in critical-creative milieus and among young idealists (all p < 0.001). Environmental affect, environmental knowledge, and gender were significantly associated with environmental cognition. In precarious milieus, environmental behavior was significantly lower than in traditional milieus and critical-creative milieus and among young idealists (all p < 0.001) and was significantly associated with environmental affect.ConclusionThe differences in the perception of environmental health burdens, environmental knowledge, and environmental awareness among precarious milieus indicate that there is a need for specific education and support structures for these population groups. Further research is needed to determine what other factors within the precarious milieus influence environmental knowledge and awareness, as well as the skills needed to understand environmental information, which are included in the framework of environmental (health) literacy.